Utilizing Mathematical Modelling and Offloading to Conduct Crowdsensing in A Collaborative Setting - P. Ananthi (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Crowdsensing is an emerging field where sensing is performed by a large number of devices distributed in an environment. This paper presents a Collaborative Mobile Fog (CMF) environment where users deploy sensors. Each user can sense and collect data from the environment. The collected data is then processed and analyzed by a centralized server. We use Volterra integral to model Crowdsensing’s sensing process in a collaborative mobile fog environment using Volterra integral and logistic drop-offloading. Crowdsensing is an emerging field where sensing is performed by a large number of devices distributed in an environment. This paper presents a Collaborative Mobile Fog [CMF] environment where users deploy sensors. Each user can sense and collect data from the environment. The collected data is then processed and analyzed by a centralized server. We use Volterra integral to model the sensing process. There are several challenges when deploying crowdsensing systems. One challenge is that crowdsensing can be time-consuming and resource-intensive. Another challenge is that data can be difficult to process and analyze. This paper addresses these challenges using Volterra integral to model the sensing process. Volterra Integral is a software tool that efficiently processes large amounts of data. This allows us to efficiently process and analyze the data collected by the sensors in our CMF environment. We use Volterra integral to model the sensing process. Volterra Integral is a software tool that efficiently processes large amounts of data. This allows us to efficiently process and analyze the data collected by the sensors in our CMF environment. We use Volterra integral to model the sensing process. Volterra Integral is a software tool that efficiently processes large amounts of data. This allows us to efficiently process and analyze the data collected by the sensors in our CMF environment.